1996
DOI: 10.1093/rheumatology/35.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Infertility May Sometimes Be Associated With Nsaid Consumption

Abstract: Non-steroidal anti-inflammatory drugs are widely used in the treatment of inflammatory joint diseases. Many patients suffering from these disorders are young women during their childbearing years. We report three cases of infertility where the cause may have been NSAID-induced 'luteinized unruptured follicle' syndrome. This phenomenon is well recognized in obstetric circles, and we would like to bring it to the attention of rheumatologists since it is not documented in the rheumatological literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 2 publications
1
36
0
2
Order By: Relevance
“…The small percentage of follicles that do ovulate fail to be fertilized, most probably owing to impaired oocyte maturation (Lim et al, 1997). COX inhibitors, such as NSAIDs, cause reversible female infertility and may act in a similar manner (Akil et al, 1996;Pall et al, 2001;Smith et al, 1996). Like many mammals, Drosophila females also ovulate only one mature oocyte at a time, most probably by inducing contraction of the muscles surrounding just 845 RESEARCH ARTICLE Pxt encodes the Drosophila cyclooxygenase one of the more than 30 ovarioles that make up the two ovaries.…”
Section: Research Articlementioning
confidence: 99%
“…The small percentage of follicles that do ovulate fail to be fertilized, most probably owing to impaired oocyte maturation (Lim et al, 1997). COX inhibitors, such as NSAIDs, cause reversible female infertility and may act in a similar manner (Akil et al, 1996;Pall et al, 2001;Smith et al, 1996). Like many mammals, Drosophila females also ovulate only one mature oocyte at a time, most probably by inducing contraction of the muscles surrounding just 845 RESEARCH ARTICLE Pxt encodes the Drosophila cyclooxygenase one of the more than 30 ovarioles that make up the two ovaries.…”
Section: Research Articlementioning
confidence: 99%
“…Dysfunctional ovulation was observed in half of the patients treated with lower dose and ninety percent in the patients treated with higher doses of meloxicam (21). Also in another study complete inhibition of ovulation has been achieved by 150-200 mg of indomethacin (22). This indicates that prostanoids must be reduced below a certain threshold to result in LUF syndrome.…”
Section: Percentage Reduction In Ovulation By Diclofenac Naproxen and mentioning
confidence: 93%
“…Dysfunctional ovulation was observed in 11 (50%) of 22 cycles treated with 15 mg/day and 20 (90.9%) of 22 cycles treated with 30 mg/day of meloxicam (16). Complete inhibition of ovulation has been achieved by 150 -200 mg of indomethacin (5,9). This indicates that prostanoids must be reduced below a certain threshold to result in LUF syndrome.…”
Section: Micu Et Almentioning
confidence: 99%
“…Previous studies comprising series of healthy women and case reports of women with rheumatic diseases (1,(5)(6)(7)(8)(9)(10)(11) demonstrated the occurrence of the LUF syndrome with exposure to inhibitors of cyclooxygenase 1 (COX-1) and COX-2. Placebo-controlled studies of healthy women exposed to NSAIDs showed delayed rupture of the follicle, but no modification of the hormonal cyclicity, although a decrease of progesterone was observed in some studies (5,7).…”
Section: Introductionmentioning
confidence: 99%